THE RELEVANCY INTER-MARKET THEORY TO EXPLAIN GLOBAL FINANCIAL CRISIS - Iman Heru Wijayanto; Albert Hasudungan (FIRM Journal of Management Studies, 2016)
This research will examine the relevancy of the inter-market theory to describe the relationship among financial market variables in the inflationary stage, where the global crisis happens.  From the empirical finding, the relationship between stock and commodities prices is relevant with the inter-market theory. Furthermore, inter-market theory is similar with the empirical relationship between exchange rates and commodities. However, empirical relationship between commodities and bonds prices is not relevant with the relationship in the inter-market theory. This irrelevant relationship respectively occurs in the relationship between bonds and stocks prices. A quantitative method by using secondary data is used to explain correlation among these markets. Therefore, inter-market theory needs to be complement with other theories to explain such irrelevant relationship between financial market variables.